Factors influencing root resorption in retained mandibular second deciduous molars with congenital absence of second premolars: a cross-sectional study - Keita Ishizuka; Chiho Kato; Akiyo Fujita; Eri Misawa-Omori; Takashi Ono (SpringerOpen, 2024)
Abstract Background There are currently no studies that quantitatively compare the relationship of root resorption to the patient's systemic history or craniofacial and intraoral morphology, especially in relation to possible host factors. Thus, this study aimed to clarify the factors associated with root resorption in retained mandibular second deciduous molars with the congenital absence of second premolars and predict the prognosis of retained mandibular second deciduous molars. Methods A cohort of 5547 patients who visited the orthodontic clinic at Tokyo Medical and Dental University Dental Hospital between 2013 and 2022 was screened. Lateral cephalometric radiographs, panoramic radiographs, upper and lower dental models, and orthodontic treatment questionnaires were used as reference materials to apply the inclusion and exclusion criteria. Ultimately, 111 patients were included in the analyses. The patients were divided into two groups based on the root resorption levels of the retained mandibular second deciduous molars. Those with less root resorption were classified under the good condition (GC) group, whereas those with more root resorption were classified under the poor condition (PC) group. Demographic, clinical, and cephalometric parameters were compared between the groups. A multivariate logistic regression model was used to predict the probability of root resorption. Results The prevalence of congenitally missing mandibular second premolars with persistent mandibular second deciduous molars was 2.0%. In a total of 111 patients, eighty-three teeth (53.2%) were classified into the GC group, whereas 73 teeth (46.8%) were classified into the PC group. The Frankfort-mandibular plane angle (FMA) [odds ratio (OR): 0.87], Frankfort-mandibular incisor angle (FMIA) (OR: 0.93), overbite (OR: 1.38), adjacent interdental space (OR: 1.46), distance from occlusal plane (OR: 0.80), and caries treatment (OR: 7.05) were significantly associated with the root resorption of the retained mandibular second deciduous molars. Conclusions Our findings suggest that skeletal morphology, oral morphological patterns, and history contribute to root resorption in retained mandibular second deciduous teeth with congenital absence of subsequent permanent teeth.